Application of Biosand Filter with the Addition of Activated Carbon Media in Domestic Wastewater Management in Kradenan Tingkir Village, Salatiga City - Toat Kilang Widi Sasongko; Gaezka Ardhika Putra; Dewi Setiyaningsih; Felice Abigail Setiadi; Pebri Iman Telaumbanua; Marchella Glory Putricia (International Journal Labs, 2025)
The scarcity of clean water due to domestic wastewater contamination has become a serious issue for the residents of Kradenan Village, Tingkir District, Salatiga City. One potential solution to address this problem is the use of a biosand filter enhanced with activated carbon as an additional filtration medium. The inclusion of activated carbon has proven to offer a sustainable approach to clean water access, utilizing simple and locally available materials. The objective of this study is to design and evaluate a domestic wastewater treatment system in the form of a biosand filter with added activated carbon media, specifically for Kradenan Hamlet, Tingkir District, Salatiga City. This innovation is expected to offer a sustainable solution to the limited access to clean water in the region. In addition to the filter design, the study evaluates the quality of the filtered water by measuring parameters such as pH, turbidity, Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD), color, and odor to assess the effectiveness of the filtration media in improving water quality to meet acceptable clean water standards. The method involves constructing a biosand filter comprising layers of gravel, coarse sand, fine sand, and activated carbon enclosed within a biofilm, all assembled inside a container. The water used in this study was sourced from the Cengek River in Kradenan Hamlet, originating from the Senjoyo spring. The modified biosand filter with activated carbon is expected to serve as an innovative approach to managing domestic wastewater in both rural and urban areas.